Covid-19 Pandemic and Welfare of Fishermen Kamal Muara - Wendra Afriana; Amanah Abdulkadir; Harry Azis (Journal of Business and Behavioural Entrepreneurship, 2021)
This paper aims to find out the right and fast strategy in anticipating the decline in the welfare of fishermen Kamal Muara during the Covid-19 pandemic. The research used SAST, AHP, and ISM analysis methods. Based on the results of ISM processing, it shows that the most appropriate and quick strategy is to provide subsidies for fishermen's losses due to large-scale social restrictions (PSBB). Second, providing training programs for processing derivative products and training on sales digitization. Third, with digital marketing training to optimize the marketing of their fish catch while ensuring the safety of anglers at work. The government's role, in this case, is not only in budget allocation but also fosters and assists so that anglers can be adaptive to technology in every fishing activity.